NATURE OF FINANCIAL SECURITY OF THE BANKING SYSTEM - BARANOVSKYI, Oleksandr; LAGNO, Anastasia (Scientific journal «World of Finance», 2023)
Introduction. The significance of the increased attention to the in-depth study of the financial security (FS) of the banking system is caused by the place and role of the banking system in ensuring the FS and investment growth of the national economy, the organization of payment turnover and the stability of the monetary system, ensuring the stability of the national currency and its purchasing power, targeting inflation and ensuring financial stability in the state. Ensuring the FS of both the banking system of Ukraine in general and its individual components, based on their paramount importance for the socio-economic development of the state, is a complex and multifaceted problem that requires constant attention.The purpose of the article is to determine the nature of the FS of the banking system.Results. Levels of security research in the banking sector are highlighted. The need to conduct such research at six hierarchical levels is emphasized. The components of FS of the banking sphere, the importance of compliance and the essence of the FS of the banking system are determined, and its author's definition is given. Aspects of consideration of FS of the banking system in general and its individual components are characterized. The main components of the FS of the banking system have been clarified. Special attention is paid to the analysis of approaches to determining financial stability, financial stability and financial reliability of the banking system and the relationship and interdependence between them. The classification of FS varieties of the banking system is presented. The factors of FS of the banking system are determined. Emphasis is placed on approaches to assessing the level of FS of the banking system.Methods. Methods of decomposition and generalization, logical analysis, abstraction, comparison, analogy are used.Conclusions. There is no unambiguous definition of the essence of the FS of the banking system, its components and varieties, aspects of their consideration, approaches to assessing the level of FS, which is necessary for the formation of an effective system of its support, the selection of the necessary approaches, methods and tools depending on the existing state of such security, which complicates the development of the specified systems. And, therefore, further research in this area is necessary.